The influence of culture on analgesic consumption: a retrospective study among Malaysian patients after breast cancer surgery - Japar, Salimah; Soh, Kim Lam; Soh, Kim Geok; Abdul Raman, Rosna (Scientific Research Publishing, 2015)
This study was carried out to determine the relationship between ethnicity/culture and analgesic consumption among patients from three main ethnic groups in Malaysia after breast cancer surgery. A retrospective study design was adopted, using medical records of 80 patients. The findings showed that the analgesic most consumed by the patients during the 48 hour post-operative period was morphine equivalents (85%), followed by non steroidal anti-inflammatory drugs (60%) and paracetamol (38%). No relationship was found between ethnicity/culture and the type or amount of analgesic consumption.